Pengaruh Kualitas Produk, Desain Produk, Green Product dan Brand Image terhadap Keputusan Pembelian Produk Kerajinan Gerabah Kasongan: - Rizky Andrian; Agus Dwi Cahya; Muinah Fadhilah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to determine the effect of Product Quality, Product Design, Green Product, Brand Image, and Purchase Decision variables. The results of the research on the t test indicate that the Product Quality variable (X1) has no significant effect on purchasing decisions with a significance value of 0.432 > 0.05 and a t count value 1.98498 < t table 4.020; Product Design variable (X2) has no significant effect on purchasing decisions with a significance value of 0.931 > 0.05 and a t-count value of 1.98498 < t table 4.020; Green Product variable (X3) has no significant effect on purchasing decisions with a significance value of 0.270 > 0.05 and a t-count value of 1.98498 < t table 4.020; Brand Image variable (X4) has no significant effect on purchasing decisions with a significance value of 0.451 > 0.05 and a t-count value of 1.98498 < t table 4.020. Based on the results of the F test, the variables of product quality, product design, Green Products and Brand Image simultaneously do not have a positive effect on the purchasing decision variables, because the significance value is 0.681 > 0.05. Keywords : Product Quality, Product Design, Green Product, Brand Image, Purchase Decision